Weight gain and tumour necrosis factor‐alpha inhibitors in patients with psoriasis. (25th October 2013) - Tan, Eugene; Baker, Christopher; Foley, Peter
Abstract: Objectives: To compare the effect of anti‐tumour necrosis factor (TNF)‐α therapies with agents that do not target TNF‐α on bodyweight and body mass index (BMI) in patients with psoriasis. Methods: A retrospective analysis of patients from the Skin and Cancer Foundation and St Vincent's Hospital Melbourne. Bodyweight and BMI were compared at baseline and weeks 12, 24 and 48. Results: A total of 143 patients were studied, equating 286 treatment courses in all. Of these, 178 courses were with an anti‐TNFα agent (54 on adalimumab, 61 on etanercept and 63 on infliximab) and 108 courses were on non‐anti‐TNFα agents (73 on efalizumab and 35 on ustekinumab). Anti‐TNFα therapy with adalimumab and infliximab resulted in weight gain from week 12 until week 48. At week 12 the infliximab group gained 1.7 ± 4.7 kg and adalimumab group gained 1.5k ± 4.5 kg. This effect persisted at week 24 (infliximab: 3.4 ± 5.7 kg; adalimumab: 2.2 ± 4.4 kg) until the end of the study (infliximab: 1.3 ± 2.9 kg; adalimumab: 2.4 ± 6.4 kg). There was a trend for weight gain in the etanercept group that did not reach statistical significance. Therapy with ustekinumab and efalizumab did not result in weight gain. Conclusion: Therapy with adalimumab and infliximab is associated with a significant increase in bodyweight and BMI.